2018
DOI: 10.5380/rf.v48i3.55492
|View full text |Cite
|
Sign up to set email alerts
|

PARTITIONING OF RAINFALL IN EXPERIMENTAL PLANTATIONS OF Eucalyptus urophylla AND Pinus elliottii

Abstract: In a period of 36 months, the partitioning of rainfall was studied in plantations of 30-year-old Eucalyptus urophylla and Pinus elliottii cultivated in flat drainage lysimeters. Gross precipitation was measured with one rain gauge installed in an open area located near the plantations; throughfall was determined by the arithmetic mean of five rain gauges located under the canopy of each species; stemflow was obtained with polyurethane foam collars connected to plastic containers installed on four trees of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Considering the species in the present study, Eucalyptus urophylla, Arcova et al (2018) reported 89.0%, 5.4% and 5.6% for throughfall, stemflow and canopy interception for a stand at 30-year-old, respectively. Souza et al (2019) for the same species but at 1-year-old found 95.3; 1.3 and 4.3% for treatment with less fertilizer applied and 91.7; 3.2 and 6.2% for treatment with greater amount of fertilizers applied.…”
Section: Introductionmentioning
confidence: 55%
“…Considering the species in the present study, Eucalyptus urophylla, Arcova et al (2018) reported 89.0%, 5.4% and 5.6% for throughfall, stemflow and canopy interception for a stand at 30-year-old, respectively. Souza et al (2019) for the same species but at 1-year-old found 95.3; 1.3 and 4.3% for treatment with less fertilizer applied and 91.7; 3.2 and 6.2% for treatment with greater amount of fertilizers applied.…”
Section: Introductionmentioning
confidence: 55%
“…In the same plot of 400 m 2 , 3 trees were selected in which stemflow water collectors (Sf) similar to those used by Arcova (2003), Arcova et al (2018) and Honda (2013). These were made of expanded polyurethane surrounding the tree trunks.…”
Section: P = Tf + Sf + Imentioning
confidence: 99%
“…A study with the same species Eucalyptus urophylla, at the age of 30, in the southeast region of Brazil was developed by Arcova et al [33]. Over 3 years of monitoring, the researchers showed that the canopy interception was 5.6%, stemflow of 5.4% and throughfall of 89%.…”
Section: Regression Analysismentioning
confidence: 99%